Role of machining defects and residual stress on the AISI 304 fatigue crack nucleation. Issue 4 (19th September 2014) - Yahyaoui, H.; Ben Moussa, N.; Braham, C.; Ben Fredj, N.; Sidhom, H.
Abstract Machining defects as rebuilt material and dislodgement were often induced by cutting of difficult to machining AISI 304 stainless steel. Their density increases with a decreasing of cutting speed. The effect of these defects on surface topography and residual stress was evaluated by roughness and X‐ray diffraction measurements coupled with numerical simulation. The role of the rebuilt material on the distribution of fatigue crack nucleation sites was investigated by scanning electron microscope examination of post fatigue samples loaded at different imposed strain amplitudes. The association of machining defects and fatigue crack nucleation sites was attributed to the contribution of additional tensile residual stresses induced by rebuilt material rather than local stress concentration. Moreover, the fatigue crack coalescence is promoted by increasing the rebuilt material density. When the machining defect density increases from 5 to 60 particles/mm2, the fatigue life decreases from −22% to −65% with respect to the electropolished surface.